Innovative Strategies for Building Children's Spirituality: Reconstructing Islamic Religious Education in the Metaverse Ecosystem - Elsa Anjar Martiana; Muh. Ubaidillah Alghifary Slamet; Triono Ali Mustofa (Indonesian Journal of Early Childhood Educational Research (IJECER), 2024)
The post-digital transformation of education has fundamentally reshaped learning ecosystems, positioning digital technologies as integral to pedagogical practices, identity formation, and value construction. Within this context, the emergence of the metaverse introduces immersive virtual environments that profoundly influence children’s spiritual development. While virtual culture presents risks such as identity fragmentation, diminished reflective capacity, and the erosion of traditional spiritual practices, it also offers opportunities for innovative, experiential, and relational learning. This study employs a qualitative literature review to examine the intersection of post-digital education, children’s spirituality, and the metaverse, with particular attention to the reconstruction of Islamic Religious Education. Drawing on interdisciplinary scholarship in education, digital culture, spirituality, and identity studies, the article synthesizes key challenges and pedagogical possibilities arising from immersive technologies. The findings suggest that a reconstructed approach to religious education—grounded in ethical governance, experiential learning, and cultural sensitivity—can function as a strategic framework for nurturing children’s spirituality within metaverse ecosystems. The study argues that fostering spiritual well-being in post-digital contexts requires not resistance to technological innovation, but intentional pedagogical design that aligns immersive digital environments with transcendent values and holistic human development.